2019
DOI: 10.2463/mrms.mp.2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve the Conspicuity of Breast Tumors on Computed High <i>b</i>-value Diffusion-weighted Imaging

Abstract: To improve tumor conspicuity on cDWI, the quality of the source images must be improved. It may easily cause inferior conspicuity to aDWIs if high b-value cDWIs were generated from insufficient SNR images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have reported increased tumor detection in cDWI images for prostate, pancreatic, and hepatic cancer [13,15,16]. However, contradictory findings were reported by Tamura et al in a study on cDWI in breast cancer [17]. Particularly, degraded image quality remains a major limitation in cDWI [12,13,17,18].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported increased tumor detection in cDWI images for prostate, pancreatic, and hepatic cancer [13,15,16]. However, contradictory findings were reported by Tamura et al in a study on cDWI in breast cancer [17]. Particularly, degraded image quality remains a major limitation in cDWI [12,13,17,18].…”
Section: Introductionmentioning
confidence: 97%
“…However, contradictory findings were reported by Tamura et al in a study on cDWI in breast cancer [17]. Particularly, degraded image quality remains a major limitation in cDWI [12,13,17,18]. High-resolution DWI (i.e., reduced field-of-view DWI (rDWI)) has been introduced to significantly improve image quality and diagnostic certainty in pancreatic pathologies, due to reduced motion and susceptibility artifacts, as well as a more precise method of lesion detection [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, lesion visibility was not significantly different between acquired and computed images. A study by Tamura et al [ 29 ] suggested improving the conspicuity of breast tumors on computed high b-value DWI by 1.5-T MRI, and the CNR of computed DWI generated from high SNR images and a high number of excitations (NEX) was superior to that of acquired DWI. However, the CNR on computed DWI obtained using the same scanning parameters was inferior to the acquired DWI.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies have almost exclusively focused on the visibility of breast cancer [20,22,[33][34][35][36]; therefore, there is limited information on the conspicuity of benign breast lesions at high or synthetic b-values. While Chen et al [37] found no significant differences in conspicuity grades using b-values of 600, 800, and 1000 s/mm 2 , our results point to a difference in conspicuity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an improvement of tumor visibility without contrast injection could improve the cost-effectiveness of MRI [ 39 ]. However, extremely high b-values, i.e., b-1800 s/mm 2 , have a low signal which can cause lesions located on the fat tissue to be overlooked, especially if fat is poorly suppressed [ 33 ]. In light of our results, b-1200 s/mm 2 could be the best option for an optimal lesion visualization with the best conspicuity, which could enhance lesion characterization by a better correlation on ADC maps and more accurate ADC values.…”
Section: Discussionmentioning
confidence: 99%